The Impact Of E-Wallet And Social Media Adoption On The Financial Performance Of Culinary Msmes In Indonesia Post-Covid-19 Pandemic - Ida Farida (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2023)
The COVID-19 pandemic has forced culinary MSMEs in Indonesia to accelerate the adoption of digital technology, especially e-wallets and social media, in order to survive and adapt to changes in consumer behavior. However, the continued impact of this adoption on financial performance in the post-pandemic era still needs to be further researched. This study aims to analyze the partial influence of e-wallet adoption, the partial influence of social media adoption, and the synergistic influence of both on the financial performance of culinary MSMEs in post-pandemic Indonesia. This quantitative research uses an online questionnaire of 425 culinary MSME actors selected using the purposive sampling technique. Data were analyzed using multiple linear regression analysis to test the relationships between variables. The results of the study prove that the adoption of e-wallets and social media individually has a positive and significant effect on financial performance. The most important finding revealed that the synergy of the two technologies had a greater impact, being able to explain 58.9% variation in improving financial performance through the creation of an integrated digital ecosystem. This study concludes that the adoption of e-wallets and social media does not only contribute individually, but most importantly the synergy between the two in creating a digital ecosystem that is able to transform business operations and marketing of culinary MSMEs, which ultimately leads to sustainable financial performance improvements post-pandemic. The practical implications emphasize the need for an integrated strategic approach in the adoption of digital technologies.